(untitled) (GESTIÓN Y TENDENCIAS, 2018)
The president of the Chilean Association of Accountants, Alejandro Vera, is worried, as is the professional body he leads nationally. This feeling, as he has explained in various media outlets, has grown as accountants have advanced in studying and mastering the complex Tax Reform launched in September 2014 and subsequently amended by its simplification in February 2016. Accountants project that the annual tax filing season for tax year 2018 will generate many discrepancies in tax payable by taxpayers in later audits, along with the corresponding penalties. What has happened is that the complexities contained in the reform result in a decidedly challenging practice of the accounting profession —not only because of the heavy workload of the months from January to April, but because of what the rest of the year entails in terms of audits.